2000
DOI: 10.1108/01443570010343717
|View full text |Cite
|
Sign up to set email alerts
|

Managing quality: critical links and a contingency model

Abstract: Addresses quality management issues of both conceptual and practical significance. The contribution is twofold: first, conceptual issues and critical relationships which have been overlooked in the current literature are discussed, as well as their policy implications. Second, a contingency approach for managing quality is proposed to guide implementation, and to help reduce the deviations between the desired and the actual outcomes of quality programs. The contingency model developed provides a basis for adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 12 publications
0
26
0
3
Order By: Relevance
“…These studies assessed firms across industries and internationally, comparing manufacturing and service firms, focusing on small firms and within specific industries [1][2][3][4] . Typically, within an industry a few leading organizations have been early adopters who have taken initial steps in implementing quality management practices and oftentimes they have been followed by other organizations who have made additional applications and refinements of quality practices.…”
Section: Introductionmentioning
confidence: 99%
“…These studies assessed firms across industries and internationally, comparing manufacturing and service firms, focusing on small firms and within specific industries [1][2][3][4] . Typically, within an industry a few leading organizations have been early adopters who have taken initial steps in implementing quality management practices and oftentimes they have been followed by other organizations who have made additional applications and refinements of quality practices.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that contingency factors have lead to different conclusions regarding the impact of TQM practices on firm performance (Saad and Siha, 2000). , for instance, explored the extent to which context and contingency factors affect TQM implementation, but did not find supporting evidence.…”
Section: Discussion and Implications For Research And Managementmentioning
confidence: 99%
“…More recently, however, Sousa and Voss (2002) concluded that difficulties and problems with the implementation of TQM may result from a mismatch between this universal form of TQM and the particular organisational context of the organisation. The high rates of failure that have been estimated also led researchers to suggest that TQM could be context-dependent (Sitkin et al, 1994; and that, consequently, TQM implementation should be tailored to the characteristics of the organization and of its environment (Benson et al 1991;Mintzberg and Westley, 1992;Dean and Bowen, 1994;Reger et al, 1994;Sitkin et al, 1994;Saad and Siha, 2000;Voss, 2001, 2002;). This view has been supported by some researchers such as Hendricks and Singhal (2001) and Zhao et al (2004).…”
Section: Several Explanations Can Be Advanced For the Apparent Improvmentioning
confidence: 99%
“…El Control de la Calidad se asocia a una de las etapas de la evolución de la Gestión de la Calidad (Garvin, 1988;Gehani, 1993;Saad y Siha, 2000). Esta etapa se sitúa aproximadamente en 1931, cuando W. A.…”
Section: Control De La Calidadunclassified